Research on the Impact of Mountain-Valley Wind on Topographic Precipitation in the Ili River Valley Based on GPM Observations - Zhimin WANG; Wanyue FENG; Jing YANG; Yuanyuan LI; Hui WANG; Yapeng FU (Gaoyuan qixiang)
Studying the impact of valley winds on terrain precipitation is crucial for gaining a deeper understanding of the mechanism of precipitation formation under complex terrain conditions.Based on GPM/DPR data from 2014 to 2021， the connected domain method was used to identify the summer terrain precipitation system in the Ili River Valley.Combined with the 10 m surface wind data from ERA5， the precipitation process was divided into valley wind type and mountain wind type.The spatiotemporal distribution， vertical structure， and macro and micro characteristics of precipitation in these two types of "trumpet mouth" terrain were compared and analyzed.The results show that valley wind precipitation is concentrated on the windward slopes of the southern and eastern foothills of the valley， with the precipitation period mainly from noon to evening （12:00 -20:00 Beijing time， same as after）.Mountain wind precipitation is more abundant in the valley plain， with more precipitation occurring from night to morning （01:00 -06:00）.The average wind speed of valley wind （0.79 m·s-1） is 6.8% higher than that of mountain wind （0.74 m·s-1）.The average near surface precipitation rate （R） and rain top height （STH） of valley wind and mountain wind precipitation are 1.32 mm·h-1， respectively 1.15 mm·h-1， 5.90 km， 5.72 km， statistics show a positive correlation between STH and R； Under the influence of uphill winds， the R， STH， mass weighted average diameter （Dm）， and particle number concentration （dBNw） of valley wind precipitation increase under the influence of terrain uplift， reaching a maximum at an altitude of 2 -3 km.The upwelling airflow formed on the windward slope promotes the condensation and coalescence of cloud droplets into raindrops； The average dBNw of valley wind precipitation （33.5） is nearly 3% smaller than that of mountain wind precipitation （34.5）， while the average Dm of the former （1.63 mm） is 18.1% larger than that of the latter （1.38 mm）.Due to the lower radar reflectivity factor of mountain winds compared to valley winds in the liquid phase region below 0 ℃， when raindrops descend to the dry layer near the ground， the large droplets break and evaporate， resulting in more dBNw and smaller Dm.Valley winds affect the macroscopic structure and microphysical processes of terrain precipitation.In future research on identifying the potential of terrain cloud artificial precipitation enhancement and numerical simulation of fine structure of precipitation in mountainous areas， attention should be paid to the role and dynamic mechanism of valley winds.